Insights of Worsening Renal Function in Type 1 Cardiorenal Syndrome: From the Pathogenesis, Biomarkers to Treatment - Fu, Kang; Hu, Yue; Zhang, Hui; Wang, Chen; Lin, Zongwei; Lu, Huixia; Ji, Xiaoping (Frontiers in Cardiovascular Medicine, 2021)
Type 1 cardiorenal syndrome refers to acute kidney injury induced by acute worsening cardiac function. Worsening renal function is a strong and independent predictive factor for poor prognosis. Currently, several problems of type-1 cardiorenal syndrome have not been fully elucidated. First, the pathogenesis mechanism of renal dysfunction is unclear. Second, the diagnostic efficiency, sensitivity and specificity of existing biomarkers are doubtful. Third, renal safety of therapeutic strategies for AHF is still ambiguous. Based on these issues, we systematically summarized and depicted the research actualities and predicaments of the pathogenesis, diagnostic marker and therapeutic strategies of worsening renal function in type-1 cardiorenal syndrome.